THE INFLUENCE OF EDAPHIC FACTORS ON THE SCLEROPHYLLY OF MANGROVE TREE SPECIES IN SOUTHERN BRAZIL - Sereneski-Lima, Carolina; Boeger, Maria Regina; de Carvalho, Leticia Larcher (Floresta, 2022)
Mangroves are coastal ecosystems, subject to limiting environmental conditions and constituted by tree communities. The tree species have adaptations to develop under such stress conditions. The sclerophylly is a response to environments with multiple stresses. In the mangrove forests, these stresses are induced mainly by salinity, frequency of tidal influence, soil waterlogging, and nutrient limitation. The aim of the study was to establish if the degree of sclerophylly, expressed in leaf morphology and nutrient contents in tree species of mangroves is associated with edaphic and salinity conditions. The study was performed in one mangrove at Paraná state, Brazil, where two plots were sampled (fringe and interior). Leaves of 15 individuals of each species (Avicennia schaueriana, Laguncularia racemosa and Rhizophora mangle) for each plot (fringe and interior) were collected for chemical and morphological analysis. Soil samples adjacent to each selected tree were collected to perform fertility analyses. The fringe soils samples present higher carbon and organic matter, C:P ratio, pore water salinity and sand predominance. The specific leaf area (SLA) showed that species have sclerophyllous leaves in different degrees: L. racemosa > R. mangle > A. schaueriana. The different degrees of sclerophylly found among the studied species and among plots indicated that each species has its own strategies and that they manifest themselves distinctly in morphological and physiological terms, even when developing under similar environmental conditions.